2023
DOI: 10.3390/healthcare11091216
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Topspin Forehand Loop in Table Tennis: An Application of OpenSim Musculoskeletal Modelling

Abstract: Topspin is one of the most attacking strokes in table tennis, and topspin forehand loop is an effective way to score. The aim of this study was to investigate the kinematics of the lower extremities in topspin forehand loop between different levels via OpenSim Musculoskeletal Modelling. Ten elite athletes (NL1) and ten medium athletes (NL2) performed the topspin forehand loop without muscle and joint injuries. An eight-camera Vicon motion capture system was used to measure the kinematics data. During the topsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, elite players showed significantly larger maximum shoulder and forearm rotation and wrist abduction [7]. A biomechanical study of the lower limbs also concluded that elite athletes had better lower extremity drivability and stronger core and leg muscles to achieve stable control of their center of gravity [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elite players showed significantly larger maximum shoulder and forearm rotation and wrist abduction [7]. A biomechanical study of the lower limbs also concluded that elite athletes had better lower extremity drivability and stronger core and leg muscles to achieve stable control of their center of gravity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the above, previous authors observed a significant difference in topspin stroke between elite and medium athletes in the forward and complete phases. In addition, elite athletes had a total hip and knee movement in the complete phase and a better lower-extremity-driving ability during the topspin forehand loop compared to medium athletes [12]. All this process is carried out in a period that can last for less than a second in certain situations.…”
Section: Introductionmentioning
confidence: 99%